Dress and care of infants in health and illness. Issue 5 (May 1985) - Eiser, C; Town, C; Tripp, J
Abstract : The mothers of 199 infants (mean age 36.7 days) were interviewed to determine how the infant was dressed and wrapped, and how the mother would deal with illness. These data were related to measures of the infant's toe and underarm temperatures and demographic information about the family. The data did not support the hypothesis that infants with particular types of clothing or bedding were at risk of overheating and shows that most mothers dress their infants appropriately. Mothers' ideas about management of illness were often inappropriate particularly in lower socioeducational groups.